THE CONSTITUTIONAL MANDATE: EDUCATING THE NATION SOCIAL JUSTICE AND THE RIGHT TO EDUCATION IN LINE WITH THE UN SDGS - RAHMATULLAH,; AHMAD, (Proceeding International Conference on Social Sciences, 2026)
The constitutional mandate of Indonesia, which emphasises the goal of “enlightening the life of the nation”, embodies the philosophical foundation of education as a social right and a cornerstone of national progress. This study examines how educational justice and equal access to quality education align with the United Nations Sustainable Development Goals (SDGs), particularly Goal 4: Quality Education. Through a comparative analysis between Indonesia, Singapore, and Australia, this paper explores the implementation of educational equity, policy structures, and learning outcomes. The findings highlight that while Indonesia has achieved significant progress in expanding access, disparities remain in quality assurance, resource distribution, and inclusivity. The research concludes that constitutional values must be continuously reinforced through equitable and sustainable educational policies aligned with SDG principles.